Philosophy and the Analysis of Music: Bridges to Musical Sound, Form, and Reference - Ferrara, Lawrence (Westport, CT Greenwood Press, 1991)
A musical experience is marked by the synthesis of passion and rationality, emotion and understanding, and body and mind. Ferrara demonstrates that each method of musical analysis confines musical significance to a single level: formal methods explain musical syntax; phenemonological methods describe the sound-in-time; and hermeneutic approaches interpret referential meanings. Ferrara devises an "eclectic method" that provides bridges for musical sound, form, and reference. In response to the multiplicity of levels of musical significance, Ferrara's eclectic method draws upon a wide-ranging number of conventional and non-conventional approaches to musical analysis which results in a dialectic of methods. Referential meanings are concretized, clarified, and delimited by the degree to which they can be grounded in the sound-in-time and formal elements; the latter are reexamined, expanded, and enriched by referential insights. In the last two chapters, the eclectic method is tested through analyses of works by Bela Bartok and David Zinn. This book is intended for trained music listeners and performers, music analysts, musicologists, and those interested in aesthetics and the development of music and music education.
Keywords: Musical analysis; Music philosophy and esthetics